The Relationship Between Penumbral Tissue and Blood-Brain Barrier Disruption in Acute Stroke Patients Presenting in an Extended Time Window - Heidari, Parisa; Blayney, Sarah; Butler, Jarrhett; Hitomi, Emi; Luby, Marie; Leigh, Richard (Frontiers in Neurology, 2020)
Background: Penumbral brain tissue identified with multimodal imaging can be salvaged with reperfusion in an extended time window. The risk of severe hemorrhagic complications after reperfusion therapy increases with worsening disruption of the blood-brain barrier (BBB). The relationship between penumbral tissue and BBB disruption has not been previously studied. Methods: Stroke patients presenting in an extended time window without a large vessel occlusion who underwent diffusion-perfusion MRI within 24 h of last-seen-normal were included. The volume of penumbral tissue was calculated using mismatch on MRI. Mean permeability derangement (MPD) of the BBB was measured within the ischemic lesion. A target profile (TP) for treatment was defined based on the EXTEND trial. Results: 222 patients were included with a median age of 73 and 55% women. The median NIHSS was 6, the mean core volume was 14 ml, the mean ischemic volume was 47 mL and the mean mismatch volume was 33 mL. Higher MPD was significantly associated with less mismatch volume (p = 0.001). A target profile was associated with lower MPD (OR 0.97; CI 0.96:0.99; p < 0.001). Of the 105 patients who had a TP, 31 (30%) had a MPD > 20% suggesting an increased risk of hemorrhage. Thus, 33% (74/222) of patients had a favorable profile for benefit and safety. Conclusions: Patients presenting in an extended time window with a favorable penumbral profile for treatment have less severe BBB disruption. Up to a third of patients who currently go untreated could be considered for enrollment in a clinical trial of thrombolysis in an extended time window.